Interorganelle transfer and glycosylation of yeast invertase in vitro. - Haselbeck, A (1986)
Core glycosylated proteins formed in the yeast endoplasmic reticulum (ER) are transported to the Golgi body, where oligosaccharides are elongated by addition of outer-chain carbohydrate. The transport process is blocked in a temperature-sensitive secretion mutant (sec18) of Saccharomyces cerevisiae, which accumulates core glycosylated invertase (product of SUC2; EC 3.2.1.26) in the ER. To approach the molecular mechanism of this transport process, we have devised a reaction in which core glycosylated invertase, accumulated in sec18 cells, is transferred to the Golgi body in vitro. For this purpose, membranes from sec18, SUC2 cells that are also defective in an outer chain alpha-1----3-mannosyltransferase (mnnl) are mixed with membranes from a strain that contains the transferase but is deficient in invertase (MNNl, delta SUC2). Transfer is detected by the acquisition of outer-chain alpha-1----3-linked mannose residues dependent on both donor and recipient membranes. The reaction is temperature and detergent sensitive and requires ATP, GDP-mannose, Mg2+, and Mn2+, and the product invertase remains associated with sedimentable membranes. Treatment of donor, but not acceptor, membranes with N-ethylmaleimide or trypsin inactivates transfer competence. These characteristics suggest that the ER, or a vesicle derived from the ER, contributes invertase to a chemically distinct compartment where mannosyl modification is executed.